Cannabinoid therapy in athletics: a review of current cannabis research to evaluate potential real-world cannabinoid applications in sport - Thompson, E. S.; Alcorn, J.; Neary, J. P. (Sports Medicine, 2024)
The increasing legalization of Cannabis sativa plant products has sparked growing interest in their therapeutic applications. Prohibition laws established in 1937 hindered formal research on cannabis, a plant with cultural and medicinal roots dating back to 2700 BC in Chinese history. Despite regulatory hurdles, published research on cannabis has emerged; yet elite athletes remain an underrepresented population in these studies. Athletes, known for exploring diverse substances to optimize performance, are drawn to the potential benefits of cannabinoid therapy, with anecdotal reports suggesting positive effects on issues ranging from anxiety to brain injuries. This review aims to evaluate empirical published cannabis research with a specific focus on its potential applications in athletics. The changing legal landscape, especially the removal of cannabis from drug testing programs in leagues such as the National Basketball Association (NBA), and endorsements by Major League Baseball (MLB) for cannabinoid products and the National Football League (NFL) for cannabis research, reflects a shift in the acceptability of such substances in sports. However, stigma, confusion, and a lack of education persist, hindering a cohesive understanding among sports organizations, including business professionals, policymakers, coaches, and medical/training staff, in addition to athletes themselves. Adding to the confusion is the lack of consistency with cannabinoid regulations from sport to sport, within or out of competition, and with cannabis bioactive compounds. The need for this review is underscored by the evolving attitudes toward cannabinoids in professional sports and the potential therapeutic benefits or harms they may offer. By synthesizing current cannabis research, this review aims to provide a comprehensive understanding of the applications and implications of cannabinoid use in the realm of athletics.